ANALISIS PENGARUH KEPEMILIKAN INSTITUSI ASING TERHADAP VOLATILITAS RETURN SAHAM DI BURSA EFEK INDONESIA TAHUN 2014-2017 - Nisa Amelia Ramdani; Nur Diana; Muhammad Cholid Mawardi (e_Jurnal Ilmiah Riset Akuntansi, 2019)
AbstractThis research was conducted with the aim to: 1) knowing a foreign institutional ownership in conjunction with variable control (domestic government ownership, size, turnover, and leverage) effect on stock return volatility. 2) partial ownership know foreign institutions, domestic government ownership, size, turnover, and leverage effect on stock return volatility. The data used in this research is secondary data. The population used in this study are all the manufacturing companies listed on the Indonesia stock exchange (BEI) in 2014-2017. The selection of the sample using a purposive sampling. Based on the criteria, obtained 39 companies sampled in this study are then analyzed using regression data panel. Based on the results of the analysis can be put forward some conclusions as follows: 1) F test results show that foreign institutional ownership in conjunction with variable control (domestic government ownership, size, turnover, and leverage) have significant effects against the volatility of stock return. 2 t test) results show that only a positive turnover effect significantly to the volatility of stock return.  Keywords: foreign institutional Ownership, stock return volatility.